Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1534735416656051
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Inhibitory Potential and Antimetastatic Effect of Camel Urine on Breast Cancer Cells In Vitro and In Vivo

Abstract: Although it may sound unpleasant, camel urine has been consumed extensively for years in the Middle East as it is believed to be able to treat a wide range of diseases such as fever, cold, or even cancer. People usually take it by mixing small drops with camel milk or take it directly. The project aims to study the effects of camel urine in inhibiting the growth potential and metastatic ability of 4T1 cancer cell line in vitro and in vivo. Based on the MTT result, the cytotoxicity of camel urine against 4T1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 60 publications
6
21
0
Order By: Relevance
“…As expected, administration of camel milk and its exosomes significantly downregulated the expression of MMP9 and ICAM1 in tumor tissues with best improvement by exosomes. Consistent with our data, Romli et al 31 also reported lower levels of ICAM1 expression in tumor tissues of mice following administration of camel urine. Additionally, ICAM1 upregulation is correlated with metastatic and invasive ability of many cancer cells, including breast cancer.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As expected, administration of camel milk and its exosomes significantly downregulated the expression of MMP9 and ICAM1 in tumor tissues with best improvement by exosomes. Consistent with our data, Romli et al 31 also reported lower levels of ICAM1 expression in tumor tissues of mice following administration of camel urine. Additionally, ICAM1 upregulation is correlated with metastatic and invasive ability of many cancer cells, including breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that oxidative stress/antioxidant pathway may be involved in the inhibitory effects of camel milk and its exosomes on tumor progression. Consistent with this, camel urine (which also has been known to have anticancer activity) also decreased MDA levels and iNOS mRNA expression in tumor tissues of mice 31 and increased MDA levels in breast cancer patients. 32 iNOS and NO accelerate tumor growth and progression through induction of the angiogenesis and metastasis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the early 20th century, a collection of anecdotal records, “The Water of Life: A treatise on urine therapy” came to be considered the founding document of the field 4,5 . Since cancer in many cases requires agents that induce life‐threatening side effects, the possibility that a simple substance such as one's own urine could serve as a cancer treatment sparked interest 6‐9 . However, the existing body of scientific literature does not describe the therapeutic role of any specific components in urine.…”
Section: Introductionmentioning
confidence: 99%
“…Dromedary camels in most regions of Asia and Africa are used as pack animals and as a source of food for nomads and low income rural populations. Their unique ability to withstand harsh environmental conditions coupled with their medical benefits [ 5 8 ], make camels an ideal case for further studies.…”
Section: Introductionmentioning
confidence: 99%